Gender-separate education in Spain: reflections on educational rights and freedoms from a constitutional and human-rights perspective - Martínez López-Sáez, Mónica; Almenar Rodríguez, Roser (Lex Social: Revista de Derechos Sociales, 2021)
Gender-separate education, understood as a pedagogical model that provides separate schooling for boys and girls, has been subject to legal and public scrutiny for the past thirty years. Nonetheless, it has not been until 2018 that this educational option was put into the spotlight, especially regarding its constitutionality and compatibility with arts. 1.1, 9.2 and 14 of the Spanish Constitution, which constitute a manifestation of the principles of equality and non-discrimination, while at the same time trying to balance it with art. 27 of said constitutional text, with respect to the right to education and freedom to choose and create educational centers. Against this backdrop, the present paper reviews the constitutional state of play and makes further reflections from a rights-based perspective and taking into account the cultural pluralism that characterizes contemporary societies.